THE USE OF ANIMATION VIDEO TO TEACH ENGLISH AT JUNIOR HIGH SCHOOL STUDENTS - Valentinus Yoga Satyawan (JELLT (Journal of English Language and Language Teaching), 2018)
This study aims are to identify problems of teaching English to Junior High School students, implement the animation video in the learning process, describe the effect of the media to the studentsâ€™ motivation in the learning process. This research used the principle of classroom action research.Â  The subjects of this research were28 students of eight-grade students inSMP N 1 Banguntapan. There were 2 cycles applied in this research. The researcher used observation, interviews, lesson plan, and questionnaire to collect the data. The result showed that there were some problems faced by the students in the learning process such as lack of vocabulary, uninteresting learning process, less participation, and lack of grammar knowledge. The animation video was implemented as media through a lesson plan in the learning process. The implementation of the video caused the students more interested in the teaching and learning process.